SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Hydrology under change: an evaluation protocol to investigate how hydrological models deal with changing catchments - G. Thirel; V. Andréassian; C. Perrin; J.-N. Audouy; L. Berthet; P. Edwards; N. Folton; C. Furusho; A. Kuentz; J. Lerat; G. Lindström; E. Martin; et al. (Hydrological Sciences Journal, 2015)

Dependence between flood peaks and volumes: a case study on climate and hydrological controls - L. Gaál; J. Szolgay; S. Kohnová; K. Hlavčová; J. Parajka; A. Viglione; R. Merz; G. Blöschl (Hydrological Sciences Journal, 2015)

Inhibition of quantitative PCR analysis of fungal conidia associated with indoor air particulate matter - James J. McDevitt; Peter S. J. Lees; William G. Merz; Kellogg J. Schwab (Aerobiologia, 2007)

Comparative Risk Assessments for the City of Cologne – Storms, Floods, Earthquakes - G. Grünthal; A. H. Thieken; J. Schwarz; K. S. Radtke; A. Smolka; B. Merz (Natural Hazards, 2006)

Possibilities and Limitations of Interdisciplinary, User-oriented Research: Experiences from the German Research Network Natural Disasters - Bruno Merz; Jana Friedrich; Markus Disse; Jochen Schwarz; Johann G. Goldammer; Jochen Wächter (Natural Hazards, 2006)

Development of a method to detect and quantify Aspergillus fumigatus conidia by quantitative PCR for environmental air samples - James J. Mcdevitt; Peter S. J. Lees; William G. Merz; Kellogg J. Schwab (Mycopathologia, 2004)

Fundamentals of Diagnostic Mycology, F. Fisher and N. Cook. - William G. Merz (Mycopathologia, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)